2019
DOI: 10.3389/fevo.2019.00273
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Monarch Butterflies (Danaus plexippus) at Two Highway Crossing “Hotspots” During Autumn Migration in Northeast Mexico

Abstract: The contribution to annual mortality of migrating monarch butterflies (Danaus plexippus) due to collisions with vehicles is poorly understood but likely significant. Recent estimates based on a study in Texas suggests that mortality during autumn migration may be of the order of 2 million per year or about 3% of the population. However, MaxEnt models used in that study are not well suited to quantifying mortality at hotspots where monarchs are concentrated by topography such as canyons when crossing highways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Following the authors of [29], we focused on a highway along the Sierra Madre Oriental in the state of Nuevo Leon (Highway MEX 40-D, landmark km 58, Saltillo-Monterrey; 25 • 39 18.54 N, 100 • 27 12.24 W). The highway dissects the natural habitat of the region and is adjacent to the high-density urban center of Monterrey.…”
Section: Sampling Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the authors of [29], we focused on a highway along the Sierra Madre Oriental in the state of Nuevo Leon (Highway MEX 40-D, landmark km 58, Saltillo-Monterrey; 25 • 39 18.54 N, 100 • 27 12.24 W). The highway dissects the natural habitat of the region and is adjacent to the high-density urban center of Monterrey.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…Recently, Mora-Alvarez et al [29] documented a fall migration bottleneck for monarch butterflies in northeast Mexico associated with 2 major highway crossings and predicted the annual roadkill mortality of monarchs at that site to be at least 197,000 individuals. This high mortality results from the geographic concentration of the southward bound monarchs by the Sierra Madre Oriental mountains, which forces monarchs into narrow canyons intercepted by highways.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bumblebees Bombus spp. can fly distances of several kilometres (Greenleaf et al, 2007), and migrating monarch butterflies readily cross roads, mostly at heights of >6 m (Mora Alvarez et al, 2019). However, most studies that we found focus on local-scale movement of pollinators, where pollinators with shorter flight ranges might be physically unable to cross roads, or otherwise where pollinators are more likely to be deterred from crossing roads because they are responding to local cues (e.g.…”
Section: Do Pollinators Cross Roads?mentioning
confidence: 99%
“…Pollinators that attempt to cross roads at low heights may be killed by collision with vehicles. Few studies provide information on road crossing height, though Mora Alvarez et al (2019) observed that most migrating monarch butterflies crossed highways at heights of >6 m, whilst other butterfly species have been observed exhibiting resourcesearching behaviour along roads (zig-zagging low to the ground) (Severns, 2008;Skórka et al, 2013), which puts them at high risk of being hit by road traffic. Most studies estimate mortality from vehiclepollinator collisions using counts of dead insects along roads, which are likely to underestimate (e.g.…”
Section: Q3) How Much Do Vehicle-pollinator Collisions Affect Pollinamentioning
confidence: 99%
“…The western population faces additional threats such as loss of overwintering or breeding habitat from climate-related fire and drought (Griffiths and Villablanca, 2015;Pelton et al, 2016). Furthermore, both populations face the threats of road kill mortality (Kantola et al, 2019;Mora Alvarez et al, 2019), diseases, parasitism, and predation (Altizer and de Roode, 2015;Oberhauser et al, 2015). Each of these threats contributes to the current and future resiliency of eastern and western monarch populations through population-specific responses that the SSA endeavors to make explicit.…”
mentioning
confidence: 99%